Numerical validation of the experimental cyclic response of RC frames - Braz-César, M.T. (2010)
In this paper is estimated the numerical cyclic response of RC frames with and without masonry infill’s through a simplified nonlinear analysis using a commercial finite element method (FEM) package. The numerical model is based on the experiments carried out in the National Laboratory of Civil Engineering (LNEC) and the numerical and experimental results are compared to assess the accuracy of the simplified analysis for the bare frame and for the infill frame. To take into account the highly nonlinear behaviour of reinforced concrete (RC) frames due to large deformations, a numerical model based on the inelastic hinge method is used with a higher complexity of the hinge constitutive laws, which allows verifying the suitability of every hinge model to the experimental results.